PENGELOLAAN PERPARKIRAN OLEH DINAS PERHUBUNGAN KOTA PEKANBARU (Studi Pelanggaran Pelaksanaan Tugas Oleh Juru Parkir Tahun 2017) - Ramadhan, Irvan; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Parking management by the Pekanbaru City Transportation Agency is planning activities in preparing empty parking location determination materials, checking and monitoring the existence of traffic order in the form of regulating motorized vehicles in the parking location by the parking attendant in accordance with the parking attendant's obligations, as well as monitoring and cracking down parking attendants illegal (not registered). However, in the implementation of parking by a parking attendant in the field it was found that parking attendants did not have parking facilities, such as identification, identity and tickets in parking fees.The purpose of the study was to find out the parking management by the Pekanbaru City Transportation Agency (violation study of the implementation of tasks by parking attendants in Tampan District in 2017). The research method used is descriptive qualitative method with data collection instruments including interviews, observation, and documentation studies related to the research objectives.The results of the study illustrate that parking management by the Transportation Department of Pekanbaru City (violation study of the implementation of duties by parking attendants in Tampan District in 2017) has not run optimally, where planning begins with preparation of vacant parking location determination materials by surveying parking location determination or not yet there are still potential parking locations that have not been managed. The execution of duties by the parking attendant is found that the parking attendant is not in accordance with the provisions (parking attendant obligations) in carrying out tasks, such as parking without a ticket, parking attendant without parking (ID card and vest). The inhibiting factors that affect the management of parking by the Department of Transportation of Pekanbaru (violation study of the implementation of duties by parking attendants in Tampan District in 2017), among others; limited staff / personnel and operational resources of the Civil Service Office in supervising the implementation of parking attendant duties. Another factor is the behavior of parking service users who are less concerned about their rights and obligations.Â Keywords: Parking Management, Determination of Parking Locations, Parking Assistance Authority, Parking Control. Â Â